Lunfardo lexical units related to legal matters - Nowak, Joanna (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2010)
The article deals with the Argentinian slang Lunfardo which is spoken mainly in Buenos Aires, La Plata and their surroundings. The main objective of the paper is the lexicological analysis of Lunfardo lexical units related to legal matters. Lunfardo came into existence at the turn of the 19th and 20th centuries when a great amount of immigrants from different European countries came to Argentina, mainly to its capital Buenos Aires. The languages and dialects spoken by immigrants started to mix with Spanish (its Argentinian variant) and Lunfardo started to develop. The article investigates the history of this linguistic phenomenon and its present situation. It tries to characterize Lunfardo focusing on its linguistic features and social background of its users.

Artykuł dotyczy argentyńskiego slangu lunfardo, który używany jest głównie w Buenos Aires, La Placie i ich okolicach. Jego głównym celem jest analiza leksykograficzna jednostek leksykalnych lunfardo związanych z prawem, językiem prawnym i prawniczym. Lunfardo powstało na przełomie XIX i XX wieku, kiedy do Argentyny, a zwłaszcza Buenos Aires napłynęły bardzo duże liczby imigrantów z Europy. Języki i dialekty używane przez imigrantów zaczęły mieszać się z językiem hiszpańskim (jego argentyńską odmianą) i w ten sposób zaczęło rozwijać się lunfardo. Artykuł zajmuje się historią oraz obecnym kształtem tego zjawiska językowego. Charakteryzuje lunfardo koncentrując się na jego cechach lingwistycznych oraz społeczym pochodzeniu jego użytkowników.
Jednostki leksykalne lunfardo dotyczące prawa